The impact of consumer skepticism on perceived value and purchase intention of organic food - Cicciù, Bruno; Carmona, Linda Jessica De Montreuil (Revista de Administração da UFSM, 2024)
Purpose: The purpose of this paper is to evaluate the impact of consumer skepticism on the perceived value and purchase intention of organic food. Design/methodology/approach: Quantitative research was carried out through a survey applied to a sample of 404 Brazilian respondents. Data analysis included descriptive statistics and partial least squares structural equation modeling. Findings: The study confirmed the negative relationship between skepticism and the perceived value of organic food and the positive relationship between the perceived value and purchase intention. In contrast, the negative relationship between skepticism and purchase intention was not confirmed by data analysis. Practical implications: By understanding skepticism, brands can educate consumers, build trust, refine their value propositions, and differentiate their products. Effective communication strategies can showcase quality and authenticity while justifying premium prices. It is suggested to public policymakers that information campaigns be promoted to improve knowledge about health, the environment, and organic production and consumption. Social implications: Results can improve the quality of life of people through the consumption of healthy and environmentally sound food. Originality: This study can be considered one of the first to address the relationship between consumer skepticism, perceived value, and purchase intention of organic food, pointing to the influence of contextual factors, such as consumer skepticism, on consumer behavior.